ZAKAT; MUTUAL COOPERATION IN ALLEVIATING POVERTY - Angga Syahputra; Nurhayati; Reni Ria Armayani Hasibuan (IAIN Lhokseumawe, 2022)
Accumulation of wealth in a group of individuals has no benefit in the view of Islam. This only creates social jealousy and a deep gulf between the rich and the poor. Social jealousy in the end brings a lot of harm to the people. Islam has the concept of mutual cooperation in distributing wealth, so that there is economic equity. Zakat is a method of mutual cooperation in Islam to alleviate poverty. Maximizing zakat is proven to be able to help move the economy, as this tradition has been applied since the time of the Prophet and the Companions. The management of zakat that has not been maximized is a challenge for eradicating poverty at this time, even though the potential for zakat in Indonesia is very large. Not to mention the reluctance of the community to pay zakat to existing institutions, is a challenge in itself. This study uses a qualitative method by using a literature study as the source of the study. This research results that to encourage the maximization of zakat funds in Indonesia, it is necessary to improve the quality of services and education to the community so that there is a change in the perspective and public trust in existing zakat institutions